Producción orgánica de pasto de corte king grass morado (Pennisetum purpureum x Pennisetum typhoides) en el CIEY-UNAP carretera Yurimaguas Tarapoto - Saavedra Salas, Piter (2023)
The research was carried out at the CIEY, Km 17-UNAP Yurimaguas-Tarapoto highway, in order to evaluate agronomic and productive parameters of purple grass; the treatments in studies were: T1 black earth, T2 cow composting; T3 sheep composting and T4 cuyaza composting; with doses of 30 Tn/Ha, for each treatment 15 kg/5m2. Plant height, tillering, green matter, dry matter, % protein and fiber were evaluated; the statistical design used was Completely Random Blocks with 4 treatments and 4 repetitions; the results were subjected to the Tukey test with 5% error. The evaluations were carried out 45 and 60 days after the leveling cut; the height and tillering in the two evaluations did not find statistical differences between treatments; it also occurred with the green matter, being numerically higher the T4 43 Tn/Ha and T3 68 Tn/Ha with respect to the cutting time; neither were statistical differences found in dry matter, being higher T4 6.55 Tn/Ha. and T3 15.20 Tn/Ha related to cutting time. The % of protein in the first cut did not show statistical differences; in the second cut it was found. The % of fiber at 45 days did not show statistical differences, at 60 days T1 compared to T2, T3 and T4 showed differences. These results obtained indicate that, using composted organic fertilizers, the forage production available for livestock is improved, without contaminating the environment.